ANALISIS PENENTUAN SAHAM YANG AKAN DIBELI SUATU TINJAUAN UMUM - Wibowo, Edi - (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2011)
ABSTRACT Securities analysis is fundamental to note investor. This is important, because without a good and rational analysis, investors can suffer losses. Occurs when the decision to buy shares of the estimated intrinsic value is greater than the market price (undervalued). Instead the decision to sell the shares occurs when the intrinsic value which is smaller than the market price (overvalued). To analyze the securities known tehnical approach and the fundamental approach. In addition it is known also by the new approach is the concept of efficient market hypothesis or efisient market better known as modern portfolio approach. In general, three approaches are presented in this paper. Keyword: Stocks, issuers, investment, inflation